Development Model of Traditional Ritual Festivalization as Cultural Tourism Attraction in Padang Panjang City, West Sumatra - Siti Ivadhea Harrisa; Yohanes Kristanto; I Made Sendra; Rahmad Oscar Ridho (Asian Journal of Social and Humanities, 2023)
Traditional rituals were part of the daily life of the Minangkabau and Mentawai indigenous peoples in the past. Since the arrival of Islam, the understanding that has developed in Minangkabau society is "adat basandi syarak, syarak basandi Kitabullah", which means that adat refers to Shari'a, Shari'a refers to the Koran. Halal branding has become a framework for developing tourism in West Sumatra which has resulted in tensions with the indigenous Mentawai people who do not adhere to Islam. The Festival Ritual Nagari raised in this thesis raises both rituals from the culture of the Minangkabau and Mentawai indigenous peoples. This thesis discusses the festivalization of traditional rituals carried out in the city of Padang Panjang, West Sumatra. This research aims to enrich cultural tourism attractions that are inclusive of Mentawai traditional culture so as to achieve the common goal of increasing visitors to West Sumatra. This research was conducted in a qualitative descriptive manner with cultural thematic analysis methods. In-depth interviews were conducted with stakeholders involved in developing the traditional ritual festival in Padang Panjang. The results of this study indicate that the development of traditional rituals as a cultural tourism attraction requires a development model so that the ritual festivals carried out can be sustainable. This study shows that the collaboration of stakeholders greatly influences the continuity of traditional ritual festivals. In addition to the development model, an event management flow chart for the Festival Ritual Nagari 2 and the 2023-2026 Nagari Festival Ritual event calendar were also found. The active collaboration of all stakeholders is suggested so that the Festival Ritual Nagari can be carried out continuously in the future. The establishment of regulations regarding the festival of traditional rituals is needed because it does not only function as a cultural tourism attraction but also cultural diplomacy.